Motivational factors' relationships with sports and exercise participation of students at a Singapore University - Guo, Deborah Weixian (2014)
The present study examined the relationships of motivational factors with sports and exercise participation in Singaporean college students and used an extended hypothesized motivational model to explore the mechanism of the motivational factors. 289 participants aged 21 to 36 years old were included in the study. Participants filled up a survey instrument, which included validated measures of personality, life goals, participatory motives, regulatory motives and participation scores. A study description and informed consent were provided in accordance with University guidelines prior to survey administration. Competition motive was the best predictor of sports participation (beta = 0.364, p < 0.05). Conscientiousness at beta value (beta = 0.237, p < 0.05) and Popularity life goal at beta value (beta = 0.214, p < 0.05) best predicted exercise participation. Correlations among motivational factors were also observed. Motivational factors for sports participation tend to be more automated than exercise participation, which may better promote long-term adherence for physical activity. While relevant authorities may employ the initial use of social media platforms to encourage exercise participation, emphasis should be placed on intrinsic variables as they surface. Relationships among motivational factors for sports and exercise participation are different and should be examined separately for future studies. Future studies can further examine important predictors of physical activity for the Asian college students and explore the hypothesized motivational model using structural equation model.